A comparison between the ley general para la inclusión de las personas con discapacidad and the americans with disabilities act - Prieto Armendáriz, Elvia Susana; Saladin, Shawn Patrick (UANL Facultad de Trabajo Social, 2012)
The purpose of this study is to understand more about the currently enacted Ley General para la Inclusión de las Personas con Discapacidad (General Law for the Inclusion of People with Disabilities) in Mexico and compare it to the Americans with Disabilities Act (ADA) in the United States. There is a difference in historical events that occurred in each country that lead to the passing of each law. The understanding of the Mexican disability background is helpful for disability advocates and anyone in this field to be able to understand where Mexican citizens with disabilities are coming from when they seek services in the United States. Due to the Mexican law being passed in May 2011 there is not enough information that provides criticism to the effectiveness of the law and how it has impacted its citizens.